Characteristics Of Filament From Extrusion Result Of Low Density Polythylene Plastic Waste Using Extrusion Method For 3d Printing Filament Applications - Muhammad Ali Chandra; Onny Sutresman; Fauzan Djamaluddin (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2025)
Low-Density Polyethylene (LDPE) plastic is a material that is widely used by the industry as packaging. Worse, the manufacturing industry players do not place environmental issues as the main focus in the supply of products. This study aims to analyze the characteristics of LDPE plastic waste that is formed into filaments for 3D printing filament applications. The research variables analyzed were the temperature of the test sample at 170 °C, 180 °C, 190 °C, 200 ºC, 210 °C, and 220 °C. The filament analysis process is to form LDPE plastic waste into 3D printing filaments using a plastic waste extrusion machine. The hardness test was then carried out using a digital Shore A Durometer Hardness tool. Furthermore, a microstructure test was also carried out using SEM (Scanning Electron Microscope). The results of the hardness test obtained show that the specimen temperature of 210 °C has the highest hardness value, which is in the range of 83–89.5 HA. In the meantime, specimens at 180 °C had the lowest hardness values, ranging from 59.5 to 71.5 HA. In addition, the SEM test resulted in the sample surface not being very flat at temperatures of 170 °C, 180 °C, and 190 °C, while the sample surface was quite flat at temperatures of 200 °C, 210 °C, and 220 °C.